2010
DOI: 10.5194/cp-6-115-2010
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to stable water isotopes in climate models: benefits of forward proxy modelling for paleoclimatology

Abstract: Abstract. Stable water isotopes have been measured in a wide range of climate archives, with the purpose of reconstructing regional climate variations. Yet the common assumption that the isotopic signal is a direct indicator of temperature proves to be misleading under certain circumstances, since its relationship with temperature also depends on e.g. atmospheric circulation and precipitation seasonality. Here we introduce the principles, benefits and caveats of using climate models with embedded water isotope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 31 publications
3
105
0
3
Order By: Relevance
“…Because the stable hydrogen and oxygen isotope ratio of water vapor, liquid and ice reflects the balance of processes influencing regional hydrology, measurements of the oxygen and hydrogen isotope ratios of water can provide constraints for water balance studies and expose model shortcomings (Jouzel and Merlivat, 1984;Henderson-Sellers et al, 2004;Henderson-Sellers, 2006;Sturm et al, 2010). The utility of isotope ratio information stems from the fractionation that accompanies phase changes in which the heavier isotopologues preferentially remain in liquid or solid form during evaporation and condensation (Bigeleisen, 1961;Dansgaard, 1964).…”
Section: Noone Et Al: Water Sources In the Boundary Layermentioning
confidence: 99%
“…Because the stable hydrogen and oxygen isotope ratio of water vapor, liquid and ice reflects the balance of processes influencing regional hydrology, measurements of the oxygen and hydrogen isotope ratios of water can provide constraints for water balance studies and expose model shortcomings (Jouzel and Merlivat, 1984;Henderson-Sellers et al, 2004;Henderson-Sellers, 2006;Sturm et al, 2010). The utility of isotope ratio information stems from the fractionation that accompanies phase changes in which the heavier isotopologues preferentially remain in liquid or solid form during evaporation and condensation (Bigeleisen, 1961;Dansgaard, 1964).…”
Section: Noone Et Al: Water Sources In the Boundary Layermentioning
confidence: 99%
“…The model is based on the Community Atmosphere Model version 3 (CAM3) (Collins et al, 2006), and the isotope module was developed by David Noone, University of Colorado. More details of isoCAM3 can be found in Noone and Sturm (2010) The isoCAM3 model has been applied in several studies that investigated the isotopic response to past climate changes (Tharammal et al, 2013;Speelman et al, 2010;Sturm et al, 2010;Pausata et al, 2011;Liu et al, 2012;Sewall and Fricke, 2013;Liu et al, 2014).…”
Section: The Model Isocam3mentioning
confidence: 99%
“…Such isotope-enabled AGCMs provide a mechanistic understanding of the atmospheric processes influencing the isotopic composition of meteoric water. Since the pioneering work of Joussaume et al (1984), Jouzel et al (1987), Hoffmann et al (1998) and others, about a dozen stateof-the-art GCMs have been equipped with explicit isotope diagnostics (see Sturm et al, 2010, for a detailed model overview). A number of studies have clearly demonstrated their usefulness for an improved climatic interpretation of present and past water isotope variability (e.g.…”
Section: Introductionmentioning
confidence: 99%